Training Profession for Law Career on Facing ASEAN Economic Community Era: Improving the Law Graduates through Development of Legal Education Method - Khotijah, Farah Diba; Mawardi, Anas; Sholihah, Inayatus (The Indonesian Journal of International Clinical Legal Education, 2019)
The ASEAN Economic Community (AEC) is one of the largest marketshare in-Southeast Asia. International product or service trade involvingten countries in Southeast Asia. The AEC will provide a free movementto international product and service for ten countries in Southeast Asia.The condition of the human resources (HR) and employment becomeone of the challenges this faced by Indonesia. High competition ofgraduates also cannot avoid on this AEC era. As well as, law graduates,will face challenge in this era. Based on data BPS 2016 more than 2500graduates have not found appropriate work or carrier. Creating aqualified law graduates face on era of the MEA is required thedevelopment of a method of legal education, one of which, namely theexistence of Training Profession for a Law Career. Training professioncarried out by institutions training profession formed the University astraining for law graduates who do not continue the second strata (S2)as well as having direct orientation for entering into society and work.Its implementation required for graduates of law during a certain timeto experiment, whereas after that each are given the freedom to addjust our assessment for more steeped in the profession or does notproceed and immediately dove into the community. Through thesupport of education and skills enhancement, labor productivity will beincreased so that it can encourage the improvement of nationalcompetitiveness.